1994
DOI: 10.1086/646887
|View full text |Cite
|
Sign up to set email alerts
|

Quality Standard for Antimicrobial Prophylaxis in Surgical Procedures

Abstract: The Quality Standards Subcommittee of the Clinical Affairs Committee of the Infectious Disease Society of America (IDSA) developed the standard. The subcommittee was composed of representatives of the IDSA (Drs. Gross and McGowan), the Society for Hospital Epidemiology of America (Dr. Wenzel), the Surgical Infection Society (Dr. Dellinger), the Pediatric Infectious Disease Society (Dr. Krause), the Centers for Disease Control and Prevention (Dr. Martone), the Obstetrics and Gynecology Infectious Diseases Socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
160
1
18

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(180 citation statements)
references
References 35 publications
1
160
1
18
Order By: Relevance
“…A study by Stone et al showed that the SSI rate was almost identical in surgical procedures where the first dose of antibiotic was given postoperatively and in those without antibiotic prophylaxis [14]. Thus, initiation of antibiotic prophylaxis postoperatively is not recommended [6]. Around 80% of the prophylactic antibiotics were administered within one hour prior to the surgical incision in our study, which were concordant with the guideline.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A study by Stone et al showed that the SSI rate was almost identical in surgical procedures where the first dose of antibiotic was given postoperatively and in those without antibiotic prophylaxis [14]. Thus, initiation of antibiotic prophylaxis postoperatively is not recommended [6]. Around 80% of the prophylactic antibiotics were administered within one hour prior to the surgical incision in our study, which were concordant with the guideline.…”
Section: Discussionsupporting
confidence: 84%
“…In American hospitals, more than half of patients (59.3%) had generally continued antibiotic prophylaxis for more than 24 hours after the surgery ended [15]. In fact, the optimal duration of antibiotic prophylaxis is not known, but is generally recommended to be discontinued within 24 hours following the operative procedure [6,7,13] The unnecessary and prolonged use of prophylactic antibiotics is associated with the emergence of resistant pathogens and increased cost of medical care [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The timely administration of prophylactic antibiotics, a practice now underpinned by its inclusion in the recently promulgated WHO's Safe Surgical Checklist,3 is considered an essential component of infection control 4 5. Unfortunately, such prophylaxis does not completely eliminate healthcare-associated infections and as antibiotic resistance is increasing6 there is every reason to adopt all reasonable steps to reduce contamination in the first instance.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect in gynecology oncology and in surgery in general is to reduce the rate of surgical site infections (SSIs) which occur for 40 % of all noso comial infections in surgical patients and occur in up to 20 % of patients undergoing abdominal surgery; there is a twofold increase in mortality in surgical patients with SSIs [2]. It is widely accepted that preoperative that factors which increase preoperative infection rate in women undergoing radical pelvic surgery are associated with elongation of duration of surgery, patient's performance status, anemia, nutritional status, history of post surgical infections, metabolic diseases, presence of malignancy, post irradiation and post chemotherapy status, obesity etc [3].…”
mentioning
confidence: 99%